Design and development of a digital shared decision-making tool for stroke prevention in atrial fibrillation. Issue 1 (2nd February 2023) - Nunes, Julio C; Baykaner, Tina; Pundi, Krishna; DeSutter, Katie; True Hills, Mellanie; Mahaffey, Kenneth W; Sears, Samuel F; Morin, Daniel P; Lin, Bryant; Wang, Paul J; Stafford, Randall S
Abstract: Background: Shared decision-making (SDM) is an approach in which patients and clinicians act as partners in making medical decisions. Patients receive the information needed to decide and are encouraged to balance risks, benefits, and preferences. Informative materials are vital to SDM. Atrial fibrillation (AF) is the most common cardiac arrhythmia and responsible for 10% of ischemic strokes, however 1/3 of patients are not on appropriate anticoagulation. Decision sharing may facilitate treatment acceptance, improving outcomes. Aims: To develop a framework of the components needed to create novel SDM tools and to provide practical examples through a case-study of stroke prevention in AF. Methods: We analyze the design values of a web-based SDM tool created to better inform AF patients about anticoagulation. The tool was developed in partnership with patient advocates, multi-disciplinary investigators, and private design firms. It was refined through iterative, recursive testing in patients with AF. Its effectiveness is being evaluated in a multisite clinical trial led by Stanford University and sponsored by the American Heart Association. Findings: The main components considered when creating the Stanford AFib tool included: design and software; content identification; information delivery; inclusive communication, user engagement; patient feedback; clinician experience; and anticipation of implementation and dissemination. We also highlight the ethical principles underlying SDM; matters of diversity and inclusion, linguistic variety, accessibility, and health literacy. The Stanford AFib Guide patient tool is available at: https://afibguide.com and the clinician tool at https://afibguide.com/clinician . Conclusion: Attention to a range of vital development and design factors can facilitate tool adoption and information acquisition by diverse cultural, educational, and socioeconomic subpopulations. With thoughtful design, digital tools may decrease decision regret and improve treatment outcomes across many decision-making situations in healthcare. Lay Summary: Better healthcare results when patients and clinicians act as partners in making medical decisions. Atrial fibrillation is a common heart rhythm problem that increases the risk of stroke. This risk can be mitigated by taking blood thinning medications. Using a user-centered design strategy with the goal of improving treatment understanding and acceptance, we created a digital decision-making aid with modules for patients to use ahead of doctor's visits and for clinician use during visits. The tool was developed in partnership with patient advocates, multi-disciplinary investigators, and private digital design firms. The main components considered when creating this tool included: design and software; content identification; information delivery; user engagement; inclusive communication; patient feedback; clinician experience; and anticipation of implementation and dissemination. The Stanford Afib Guide is available in English and Spanish at an eighth grade reading level at https://afibguide.com/ . A central feature is the use of a cartoon video that presents information and anticipates patient concerns without requiring the reading of text. These factors facilitate tool adoption and information acquisition by diverse cultural, educational, and socioeconomic subpopulations. The tool's effectiveness is now being evaluated in a multisite randomized clinical trial.